Tactile C fibers and their contributions to pleasant sensations and to tactile allodynia - Liljencrantz, Jaquette; Olausson, Håkan (Frontiers in Behavioral Neuroscience, 2014)
In humans converging evidence indicates that affective aspects of touch are signaled by low threshold mechanoreceptive C tactile (CT) afferents. Analyses of electrophysiological recordings, psychophysical studies in denervated subjects, and functional brain imaging, all indicate that CT primary afferents contribute to pleasant touch and provide an important sensory underpinning of social behavior. Considering both these pleasant and social aspects of gentle skin-to-skin contact, we have put forward a framework within which to consider CT afferent coding properties and pathways - the CT affective touch hypothesis. Recent evidence from studies in mice suggests that CTs, when activated, may have analgesic or anxiolytic effects. However, in neuropathic pain conditions, light touch can elicit unpleasant sensations, so called tactile allodynia. In humans, tactile allodynia is associated with reduced CT mediated hedonic touch processing suggesting loss of the normally analgesic effect of CT signaling. We thus propose that the contribution of CT afferents to tactile allodynia is mainly through a loss of their normally pain inhibiting role.